HABITUATION OF FOUR MAGIC WORDS AS A STRATEGY TO INSTILL POLITENESS VALUES IN ELEMENTARY MADRASAH STUDENTS: PEMBIASAAN PENGGUNAAN EMPAT KATA AJAIB SEBAGAI STRATEGI PENANAMAN NILAI KESOPANAN PADA SISWA MADRASAH IBTIDAIYAH - Lathifah, Umi; Erna Zumrotun (Journal of Practice Learning and Educational Development, 2025)
This study investigates the habituation of four magic words (please, sorry, thank you, and excuse me) as a strategy to instill politeness values among second-grade students at MI Al-Ma’arif Blimbingrejo. The research was conducted using a qualitative approach with purposive sampling involving ten students categorized as active and passive, complemented by interviews with the classroom teacher. Data were collected through structured observation, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that active students used polite expressions 3–6 times per day with clear intonation and appropriate context, while passive students only used them 0–2 times daily, often hesitantly or not at all. Among the four words, “thank you” (40 times) and “please” (39 times) were most frequently used, while “sorry” (20 times) and “excuse me” (12 times) appeared less often. Interviews with the teacher emphasized the role of positive reinforcement, such as praise and smiles, in encouraging students, consistent with Skinner’s reinforcement theory. Meanwhile, students acknowledged using the words mainly in specific contexts, which aligns with Vygotsky’s view of social interaction as scaffolding for moral development. Challenges include limited habituation at home and passive student traits, reflecting Bronfenbrenner’s ecological perspective. Overall, the habituation strategy proved effective in fostering politeness and strengthening character education in elementary madrasah settings.